“MAN DOES NOT LIVE ON BREAD ALONE”: THE CREATION AND FUNCTIONING OF FACTORY WORKERS' RECREATIONAL SERVICES (1943 1945) (Fiep Bulletin - online, 2015)
This study deals with first impressions on the creation and functioning of the Factory Workers Recreational Service (SRO), an organ of the Ministry of Labor, Industry and Commerce, founded in 1943 and destined to offer leisure activities to union workers. Although we recognize the importance of the dimensions of the oppression, control and manipulation present in this period, we will not focus our analysis on them, for, besides not considering them to be determinants of the phenomenon studied, in our understanding, the relationship of domination never is symmetrical. We believe this governmental organ was not created within a cultural void and, based on Bakhtin, Chartier and Foucalt, we seek to understand it from a perspective which does not consider factory workers to be totally determined by the forces of the political regime that controlled the New State. Beginning with the presumption that its foundation is related to a group of forces in action in that period, in this writing, we analyze aspects which regard the political conjuncture, the actors involved and the objectives of the regime and of the Service and we present another possibility of investigating it in order to become more familiar with it.
Keywords: Factory Workers Recreational Service; History of Leisure; New State.